One Grand, Sweet Song. - Pickering, Sam (Texas Review Press, 2016)
One Grand, Sweet Song is a collection of familiar essays in which Sam Pickering explores libraries and woods and fields. He wanders over hills and far away--to Caribbean and Canada--but he always returns to the local, to Connecticut and his memories of a Southern childhood. He ponders writing and aging, joy and lunacy. He celebrates family and Christmas. He laughs and tells terrible lies, and jokes. He runs half-marathons, and on a farm in Nova Scotia, he tries to write his Walden. "O World, I cannot hold thee close enough!" Edna St. Vincent Millay once exclaimed. In these pages Pickering embraces his world with great love wrapping it in words and pulling it and the reader unforgettably close.